Analisis Aktivitas Belajar Siswa pada Pembelajaran Biologi Berbasis Daring di Tengah Wabah Pandemi Covid-19 di SMA Negeri 3 Panyabungan - Manna Nabila Hsb (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine how active students are in learning online biology subjects during the Covid-19 outbreak. This research uses a descriptive method and the type of research is survey. The population is students of class XI IPA of SMA Negeri 3 Panyabungan and the sample students of class XI IPA 2 and XI IPA 3. Meanwhile, the research subjects used biology teachers and students of SMA Negeri 3 Panyabungan. The instruments used in data collection are questionnaires and interviews. The results of the study showed that student activity during the online learning process at SMA Negeri 3 Panyabungan was less active. This was adjusted to the situation that occurred during the Covid-19 pandemic where learning was carried out by distance learning. During online learning, student learning activity could not be fully reached according to the indicators of student learning activity, namely: 1) Visual Activities, paying attention, reading during the learning process, 2) Oral Activities, interacting in the learning process, 3) Listening Activities, listening and actively discussing, 4) Writing Activities, collecting assignments and making summaries, 5) Drawing Activities, making summaries, 6) Motor Activities, conducting experiments, 7) Mental Activities, responding, 8) Emotional Activities, interest, joy during the learning process.